Pemeliharaan Taman Hotel: Studi Kasus di Hotel Pendopo 45 Bogor - Chrysilla, Cindy; Sukewijaya, I Made (Nandur; Vol 3 No 4 (2023), 2023)
Hotel Pendopo 45 Bogor has a garden area of 1.68 ha which in some areas of the garden has poor aesthetics and it is known that there are only 3 core gardeners. This study aims to determine the efficiency of garden maintenance and the number of gardeners required by Hotel Pendopo 45 Bogor. This research method uses a survey method. The data collected is in the form of primary and secondary data. Data collection techniques used are observation, interviews, and literature study. Based on the research results, it is known that the maintenance system used at the Pendopo 45 Hotel, Bogor, is a zone maintenance system and special maintenance. The maintenance concept used is ideal maintenance and physical maintenance. Garden maintenance activities such as sweeping, watering, pruning, drying and weeding have exceeded work capacity standards according to Arifin and Arifin (2005) except for grass sweeping and grass trimming using a carrying machine. It was also found that the need for gardeners to do the job is at least 15 gardeners. The advice given is to make a written maintenance schedule, carry out close supervision, provide garden maintenance training, and increase the number of gardener workers.